Natural selection and genetic diversity of domain I of Plasmodium falciparum apical membrane antigen-1 on Bioko Island - Ya-Nan Wang; Min Lin; Xue-Yan Liang; Jiang-Tao Chen; Dong-De Xie; Yu-Ling Wang; Carlos Salas Ehapo; Urbano Monsuy Eyi; Hui-Ying Huang; Jing-Li Wu; Dan-Yan Xu; Zhi-Mao Chen; et al. (Malaria Journal, 2019)
Abstract Background Plasmodium falciparum apical membrane antigen-1 (PfAMA-1) is a promising candidate antigen for a blood-stage malaria vaccine. However, antigenic variation and diversity of PfAMA-1 are still major problems to design a universal malaria vaccine based on this antigen, especially against domain I (DI). Detail understanding of the PfAMA-1 gene polymorphism can provide useful information on this potential vaccine component. Here, general characteristics of genetic structure and the effect of natural selection of DIs among Bioko P. falciparum isolates were analysed. Methods 214 blood samples were collected from Bioko Island patients with P. falciparum malaria between 2011 and 2017. A fragment spanning DI of PfAMA-1 was amplified by nested polymerase chain reaction and sequenced. Polymorphic characteristics and the effect of natural selection were analysed using MEGA 5.0, DnaSP 6.0 and Popart programs. Genetic diversity in 576 global PfAMA-1 DIs were also analysed. Protein function prediction of new amino acid mutation sites was performed using PolyPhen-2 program. Results 131 different haplotypes of PfAMA-1 were identified in 214 Bioko Island P. falciparum isolates. Most amino acid changes identified on Bioko Island were found in C1L. 32 amino acid changes identified in PfAMA-1 sequences from Bioko Island were found in predicted RBC-binding sites, B cell epitopes or IUR regions. Overall patterns of amino acid changes of Bioko PfAMA-1 DIs were similar to those in global PfAMA-1 isolates. Differential amino acid substitution frequencies were observed for samples from different geographical regions. Eight new amino acid changes of Bioko island isolates were also identified and their three-dimensional protein structural consequences were predicted. Evidence for natural selection and recombination event were observed in global isolates. Conclusions Patterns of nucleotide diversity and amino acid polymorphisms of Bioko Island isolates were similar to those of global PfAMA-1 DIs. Balancing natural selection ...